Default, credit growth, and asset prices - Segoviano, Miguel A.; Goodhart, C. A. E. (Charles Albert Eric); Hofmann, Boris (IMF working paper ;, 2006)
This paper uses a Merton-type estimate of the probability of default (PoD) for the main banks in a sample of Organization for Economic Cooperation and Development and middle-income countries as a proxy for the fragility of their banking systems. Based on theory and stylized facts, the paper explores a range of financial and real variables that explain such PoDs across time. We find property price fluctuations and bank credit to be important explanatory factors. There is two-way interaction between these variables and a clearer relationship when the variables are entered as a deviation from trend. The lag structure between such developments and PoDs is long and varies widely across countries. The paper assesses the implications of these findings for economic policy.